"Back to Square One": The Experience of Straddling Adolescence and Early Adulthood in Unemployed UK University Graduates With Common Mental Health Issues: An Interpretative Phenomenological Analysis. Issue 4 (August 2018) - Cockshott, Christopher J.; Kiemle, Gundi; Byrne, Paula; Gabbay, Mark B.
We investigated the experiences of unemployed university graduates with common mental health issues. After conducting semistructured interviews with 12 unemployed bachelor's degree graduates with common mental health issues, we used interpretative phenomenological analysis to generate three superordinate themes: "fall from grace, " "vulnerability, " and "life on hold." Our focus in this article is life on hold and its constituent themes: "stagnation, " "moving backward, " and "feeling left behind." Graduates struggled to complete the broader structural life transition from university student to the adult world of work, experiencing a nebulous state of straddling adolescence and early adulthood. This undermined their sense of adult maturity, leaving them vulnerable to becoming entrenched in their mental health-related difficulties. We discuss these findings in relation to the developmental perspectives of life-course theory, status passages, and separation–individuation in early adulthood, which raise important issues for the applicability of life-course frameworks for these graduates, who are a disadvantaged minority group.